The effect of Phonological Encoding Complexity on Speech Fluency of Stuttering and Non-Stuttering Children - Sara Ramezani; Reza Nili-Pour; Fariba Yadegari; Mehdi Rahgozar (University of Social Welfare and Rehabilitation Sciences, 2012)
Objective: Stuttering is a fairly common speech disorder. However, the etiology is poorly understood and is likely to be heterogeneous. The aim of this research is to investigate phonological encoding complexity on speech fluency in 6-9 year old stuttering children in comparison with non-stutterers in Tehran. Materials & Methods: This cross-sectional, descriptive analytic research was done on 18 stuttering children with profound and severe level and 18 non-stuttering children. The stuttering subjects were selected by convenience and normal subjects were matched to stuttering subjects by gender, age and geographics. A non-word test comprising 87 non-words was used to investigate phonological encoding and phonological complexity effects on speech fluency. Stimuli were presented in random order with approximately 5 seconds between items, using a computer via external Toshiba SOMIC SM-818 headphone and requested subject was asked to repeat them.  Results: The results indicated that speech fluency decreased significantly (P<0.05) by increasing phonological complexity comparing to controls. Conclusion: The findings of the present research seem to suggest that, stuttering children may have deficits in phonological encoding. The deficit has been increased with phonological encoding complexity. Based on covert repair hypothesis, phonological difficulty may cause covert self- repair and leads to different patterns of stuttering.